Editorial - Ratnalikar, N. V. (Journal of Engineering Education Transformations, 2009)
Why Quality? In Engineering Education, today, everyone wants quality. Quality is considered as an imperative for more that one reason. It is required on moral grounds, as a professional demand, as a survival necessity in the competitive environment and as an accountability instrument. It is also required as a tool for self-improvement!